Waste Heat Recovery Technologies Revisited with Emphasis on New Solutions, including Heat Pipes, and Case Studies - Christodoulides, Paul; Agathokleous, Rafaela; Aresti, Lazaros; Kalogirou, Soteris A.; Tassou, Savvas A.; Florides, Georgios A. (My University, 2022)
Industrial processes are characterized by energy losses, such as heat streams rejected to the environment in the form of exhaust gases or effluents occurring at different temperature levels. Hence, waste heat recovery (WHR) has been a challenge for industries, as it can lead to energy savings, higher energy efficiency, and sustainability. As a consequence, WHR methods and technologies have been used extensively in the European Union (EU) (and worldwide for that matter). The current paper revisits and reviews conventional WHR technologies, their use in all types of industry, and their limitations. Special attention is given to alternative “new” technologies, which are discussed for parameters such as projected energy and cost savings. Finally, an extended review of case studies regarding applications of WHR technologies is presented. The information presented here can also be used to determine target energy performance, as well as capital and installation costs, for increasing the attractiveness of WHR technologies, leading to the widespread adoption by industry.
Keywords: Waste heat recovery; Energy consumption/saving; WHR limitations; EU industries; WHR Europe; WHR technologies